Phase-sensitive surface plasmon resonance sensor based on interferometric configuration - Zhang, Shuyan (2013)
Surface plasmon waves are quantized harmonic oscillatory motion of electrons at the surface. The criteria for excitation of surface plasmon resonance (SPR) are: the incident wave must be matched in angular frequency and momentum with that of the surface plasmon. [3rd Award]